2021
DOI: 10.1097/mao.0000000000003317
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease is a Risk Factor for Sensorineural Hearing Loss: A US Population Study

Abstract: Objectives: The goal of this study is to determine if chronic obstructive pulmonary disease (COPD) is associated with sensorineural hearing loss (SNHL) in a national database. Study Design: Cross-sectional study. Setting: National sample of the United States population. Patients: Adults with audiometric and spirometry data from the National Health and Nutrition Examination Study (NHANES) database. Interventions: None. Methods: A total of 2,464 adults with spirometry and audiometry data from the NHANES database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…This study did not require institutional review board approval as the NHANES database is publicly available and has deidentified patient information. The NHANES database has been widely used in a number of clinical studies (14)(15)(16)(17).…”
Section: Methodsmentioning
confidence: 99%
“…This study did not require institutional review board approval as the NHANES database is publicly available and has deidentified patient information. The NHANES database has been widely used in a number of clinical studies (14)(15)(16)(17).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have examined the association between HL and some of the specific chronic diseases included in the definition of multimorbidity. [10][11][12][13][14][15][16] For example, Sharma et al, 10 in a cross-sectional analysis of the National Health and Nutrition Examination Survey (NHANES), observed that COPD was directly associated with HL. A plausible explanation is that an inadequate supply of oxygen to the cochlea could cause ischemic lesions, hindering the conversion process of a mechanical signal to an electrical signal.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study examining the association between hearing function and multimorbidity. Previous studies have examined the association between HL and some of the specific chronic diseases included in the definition of multimorbidity 10‐16 . For example, Sharma et al, 10 in a cross‐sectional analysis of the National Health and Nutrition Examination Survey (NHANES), observed that COPD was directly associated with HL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of 16 articles published until 2018 identified a greater risk of loss of the ability to detect some sound frequencies in individuals with COPD compared to healthy individuals (6). Recently, a cross-sectional epidemiological study in the United States observed a strong association between COPD and sensorineural hearing loss (7), while a cohort study conducted in Norway identified a 50% greater chance of hearing decline in individuals with COPD (8). These studies, however, did not apply tests to identify loss of speech recognition (vocal audiometry); therefore, they did not measure whether individuals would have difficulty communicating.…”
Section: Introductionmentioning
confidence: 99%